A novel self-aggregated gold nanoparticles based on sensitive immunochromatographic assays for highly detection of opium poppy in herbal teas. (1st October 2022) - Zhang, Xuan; Wang, Jin; Liang, Jianhao; Liu, Zhiwei; Shen, Xing; Liu, Yingju; Li, Xiangmei; Xu, Zhenlin; Lei, Yi; Lei, Hongtao
Highlights: An affordable, accessible AGNPs was synthesized as highly signal labels. Two AGNPs/TRFMs-LFIA for quantitative detecting three opiates for the first time. Two highly sensitive LFIAs can be achieved quantitative analysis within 15 min. Abstract: Opium poppy abused in food has aroused public concerns due to its serious side effects. Effective monitoring is essential to fight the abuse crisis. Herein, we synthesized an easily prepared, affordable, accessible highly aggregated gold nanoparticles (AGNPs) performing in lateral flow immunoassay (LFIA) for detection opium poppy in herbal teas. Simultaneously, a LFIA based on time-resolved fluorescent microspheres (TRFMs) was developed as contrastive method. In this study, morphine (MOR), codeine (COD) and thebaine (THE) were as the specific recognition markers of opium poppy. Results demonstrated the quantitative limits of detection were 0.0049/0.0053/0.084, 0.034/0.037/0.37 ng mL −1 for AGNPs/TRFMs-LFIA, respectively. The recoveries were 95%-107.5%/91%-106.7% with coefficient of variation was 1.6%-6.6%/1.8%-7.2%, indicating excellent accuracy and precision. Parallel experiments among AGNPs/TRFMs-LFIA and LC-MS/MS analysis showed good correlation. Overall, AGNPs-LFIA executed quantitative analysis within 15 min on the basis of simple treatment while providing a rapid and sensitive analysis strategy for illegal drugs abused.